Understanding the Role of Sensorimotor Beta Oscillations - Barone, Jacopo; Rossiter, Holly E. (Frontiers in Systems Neuroscience, 2021)
Beta oscillations have been predominantly observed in sensorimotor cortices and basal ganglia structures and they are thought to be involved in somatosensory processing and motor control. Although beta activity is a distinct feature of healthy and pathological sensorimotor processing, the role of this rhythm is still under debate. Here we review recent findings of the role of beta oscillations during experimental manipulations (i.e., drugs and brain stimulation) and their alteration in ageing and pathology. We show how beta changes when learning new motor skills and its potential to integrate sensory input with prior contextual knowledge. We conclude by discussing a novel methodological alternative interpretation approach of analysing beta oscillations as a series of transient bursting events.